Praktyka obsadzania stanowisk w administracji skarbowej III RP w świetle wartości konstytucyjnych = The practice of filling tax administration positions in the Third Polish Republic in the light of constitutional values - Gadowska, Kaja (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The constitutional concept of the common good is the reason for the existence of public authorities. Administration performing state functions should serve the needs of citizens. An adequate selection of the staff who carry out state functions is a condition for a well-functioning administration. The selection is particularly important in the case of tax administration, a key link in the system of public revenue collection. The aim of this article is to analyse the weaknesses of Poland`s tax administration system. Such weaknesses have an influence on establishing professional staff.
Keywords: administracja skarbowa; obsadzanie stanowisk; dobro; służba cywilna; tax administration; filling positions; civil service; common good